2010
DOI: 10.1063/1.3531689
|View full text |Cite
|
Sign up to set email alerts
|

Shear Alfvén wave continuous spectrum within magnetic islands

Abstract: The radial structure of the continuous spectrum of shear Alfvén waves is calculated in this paper within the separatrix of a magnetic island. Geometrical effects due to the noncircularity of the flux surface's cross section are retained to all orders. On the other hand, we keep only curvature effects responsible for the beta-induced gap in the low-frequency part of the continuous spectrum. Modes with different helicity from that of the magnetic island are considered. The main result is that, inside a magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
6
18
0
Order By: Relevance
“…This study will be compared to the results of Biancalani for l = 0. 10,11 In particular, secondary resonances are expected at rational Ω surfaces where l 0 − j 0 Ω = 0. Future work will also involve studying the Alfvén spectrum numerically using the SIESTA code.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study will be compared to the results of Biancalani for l = 0. 10,11 In particular, secondary resonances are expected at rational Ω surfaces where l 0 − j 0 Ω = 0. Future work will also involve studying the Alfvén spectrum numerically using the SIESTA code.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an island on the shear Alfvén continuum have been studied in some detail by Biancalani et al [10][11][12] In Biancalani's work, a shooting method code was used to compute the spectrum. Biancalani showed that an island induces an upshift in the spectrum's minimum continuum accumulation point frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Along the whole separatrix, current spikes at scales narrower than the collisionless skin depths have been found. The importance of these effects in causing the reconnection acceleration is under investigation, and a detailed analysis will be published in a dedicated paper [18].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, as we will show later, it is easier to derive the EE contribution using equation (5). Since the resonant EEs effect of interest here can only be important during the linear growth stage of eBAE, the ZFZF generation is a forced driven process [10,18,40], and the feedback of ZFZF to eBAE will not be considered here.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In quantitative estimating the ZFZF amplitude and comparing with numerical results, e.g., Ref. [40], k Z ≡ −2i∂ r ln Φ 0 ∼ O( √ βk θ,0 ) should be used.…”
Section: Nonlinear Zfzf Generation By Ebaementioning
confidence: 99%